Conductive film, dispersion, method for producing the same, and device including the conductive film

A conductive film using semiconductor nanoparticles addresses the high manufacturing costs of precious metal-based films by achieving high conductivity in specific directions without vacuum deposition, enabling cost-effective and versatile film formation.

JP7685231B2Active Publication Date: 2025-05-29OSAKA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021552428
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-15
Filing Date
2020-10-15
Publication Date
2025-05-29
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

The manufacturing cost of conductive films using precious metals like silver nanowires and carbon nanotubes is high, and there is a need for a conductive film that can be formed without vacuum deposition methods, using non-precious metal and special carbon materials as conductive elements.

Method used

A conductive film is developed using semiconductor nanoparticles as conductive elements, which are arranged in an array portion with high conductivity in one direction (7 S/cm or more) and significantly lower conductivity in another direction (less than 10% of the primary conductivity), achieving anisotropic conductivity without the need for vacuum deposition.

Benefits of technology

The conductive film can be formed using a coating method, reducing manufacturing costs and enabling wide substrate compatibility, while maintaining high conductivity in specific directions and excellent light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007685231000003
    Figure 0007685231000003
  • Figure 0007685231000004
    Figure 0007685231000004
  • Figure 0007685231000005
    Figure 0007685231000005
Patent Text Reader

Abstract

Provided is a conductive film that can be formed without the use of a vacuum film forming method and includes, as a conductive element that achieves conductivity, a material that is neither a precious metal nor a special carbon material. This conductive film includes a semiconductor nanoparticle arrangement section. When a cross-section including the arrangement section is observed, in the arrangement section, the semiconductor nanoparticles are arranged in a row and separated from one another, and the conductivity C1 measured in at least one direction is 7S / cm or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive film, particularly a conductive film having light transmissivity. The present invention also relates to a method for manufacturing a conductive film, a dispersion for manufacturing a conductive film, and a method for manufacturing the dispersion, and further to a device including the conductive film.

Background Art

[0002] Conductive films, particularly transparent conductive films with high light transmissivity, are used in various devices as electrodes, antistatic films, and the like. Industrial mass production of conductive films is often carried out by a vacuum film-forming method typified by the sputtering method.

[0003] Since the vacuum film-forming method requires a reduced-pressure atmosphere, it has problems such as requiring large-scale equipment and having limitations on the substrates that can be used. In view of this situation, conductive films containing silver nanowires (for example, Patent Document 1 and Non-Patent Document 1), conductive films containing carbon nanotubes (for example, Patent Document 2), and the like have been proposed. These conductive films can be formed by printing methods, coating methods, etc. that do not require a reduced-pressure atmosphere.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Non-Patent Documents

[0005]

Non-Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] However, it is not easy to reduce the manufacturing cost of simple materials of precious metals such as silver nanowires and carbon nanotubes, and special carbon materials. The present invention aims to provide a conductive film that can form a film without applying a vacuum deposition method and includes a material that does not correspond to precious metals and special carbon materials as a conductive element for expressing conductivity. Another object of the present invention is to provide a method and a dispersion for manufacturing such a conductive film, a method for manufacturing the dispersion, and further a device including such a conductive film.

Means for Solving the Problems

[0007] It has been considered essential for the expression of practical conductivity that there is a conductive path formed by the conductive elements contacting each other in the film. However, according to the study by the present inventor, unexpectedly high conductivity can also be expressed from a film containing semiconductor nanoparticles separated from each other.

[0008] That is, the present invention includes an array portion of semiconductor nanoparticles, when observing a cross-section including the array portion, in the array portion, the semiconductor nanoparticles are arranged in a row in a state of being separated from each other, and provides a conductive film having a conductivity C1 measured along at least one direction of 7 S / cm or more.

[0009] The required conductivity for the conductive film may be practically sufficient if it is achieved in a specific direction. From this perspective, the conductive film does not necessarily need to exhibit a high conductivity in all directions. Based on this idea, a highly useful conductive film containing semiconductor nanoparticles as conductive elements can be obtained.

[0010] That is, from another aspect of the present invention, contains semiconductor nanoparticles as conductive elements, by the conductive element, the conductivity C1 measured along the first direction is 7 S / cm or more, Anisotropic conductivity is exhibited where the conductivity C2 measured along the second direction is less than 10% of the conductivity C1. Provided is a conductive film in which one of the first direction and the second direction is a film surface direction and the other is a film thickness direction.

[0011] Furthermore, the present invention provides a dispersion suitable for manufacturing the above-described conductive film.

[0012] That is, from another aspect of the present invention, A dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound are included. The first compound exists as an attached compound attached to the semiconductor nanoparticles and a free compound released from the semiconductor nanoparticles. Provided is a dispersion that satisfies at least one selected from i) to iv). i) The ratio of the amount of the first compound present as the free compound to the amount of the first compound present as the attached compound is 1 or more. ii) The ratio of the amount of the first compound to the total amount of the semiconductor nanoparticles and the first compound is 10% or more on a mass basis. iii) The semiconductor nanoparticles include at least one selected from oxides, sulfides, selenides, and tellurides. iv) The semiconductor nanoparticles are columnar bodies and / or polyhedrons.

[0013] Furthermore, the present invention provides a method for manufacturing a dispersion according to the present invention. This manufacturing method includes obtaining a mixed solution by mixing a stock solution containing a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, a first compound, and impurities with a solvent; applying a centrifugal operation to the mixed solution at a rotation speed of less than 5000 rpm; after the centrifugal operation, removing the solvent from the mixed solution together with at least a part of the impurities. The manufacturing method includes the above steps.

[0014] Furthermore, from another aspect of the present invention, A first ink, which is a dispersion containing a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound, wherein the first compound exists as an attached compound attached to the semiconductor nanoparticles and a free compound free from the semiconductor nanoparticles. An ink set including: a second ink containing a second compound having a molecular weight smaller than that of the first compound and capable of attaching to the semiconductor nanoparticles by substituting the first compound.

[0015] Furthermore, from another aspect of the present invention, A device including a conductive film according to the present invention, wherein the conductive film is provided as at least one functional film selected from an electrode film, an antistatic film, a heating film, and an electromagnetic wave shielding film.

[0016] From another aspect of the present invention, A device including a conductive film containing semiconductor nanoparticles and at least one electrode in contact with the conductive film, wherein the conductive film satisfies the following a) and / or b). a) including an array portion of the semiconductor nanoparticles, when observing a cross section including the array portion, in the array portion, the semiconductor nanoparticles are arranged in a row while being separated from each other, and a conductivity C1 measured along at least one direction is 7 S / cm or more. b) containing the semiconductor nanoparticles as a conductive element, due to the conductive element, a conductivity C1 measured along a first direction is 7 S / cm or more, a conductivity C2 measured along a second direction is less than 10% of the conductivity C1, and anisotropic conductivity is exhibited, wherein one of the first direction and the second direction is a film surface direction and the other is a film thickness direction.

[0017] From another aspect of the present invention, a method for manufacturing a conductive film according to the present invention is provided. This manufacturing method includes A dispersion comprising a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound, wherein the first compound exists as an attached compound attached to the semiconductor nanoparticles and a free compound free from the semiconductor nanoparticles, a first step of applying the first ink to the surface of a substrate to form a coating film; A second step of bringing a second ink containing a second compound having a molecular weight smaller than that of the first compound and capable of substituting the first compound and attaching to the semiconductor nanoparticles into contact with the coating film to substitute at least a part of the first compound in the coating film with the second compound. A method for manufacturing a conductive film comprising:

Advantages of the Invention

[0018] The conductive film according to the present invention can be formed by a method other than a vacuum deposition method, specifically, for example, a coating method, and semiconductor nanoparticles are used as a conductive element for expressing conductivity. Therefore, it can be formed on a wide range of substrates, and is advantageous from the viewpoint of reducing manufacturing costs compared to films using noble metal single materials or special carbon single materials as conductive elements.

Brief Description of the Drawings

[0019]

Figure 1

Figure 2

Figure 3

Figure 4

Figure 5

Figure 6

Figure 7

Figure 8

Figure 9

Figure 10

Figure 11

Embodiments for Carrying Out the Invention

[0020] Hereinafter, embodiments of the present invention will be described with reference to the drawings as appropriate. However, the following description is not intended to limit the present invention to specific embodiments. In this specification, the term "semiconductor" is used to mean not only ordinary semiconductors but also semimetals. A semimetal is a substance having a band structure in which the lower part of the conduction band and the upper part of the valence band slightly overlap across the Fermi level due to, for example, strain in the crystal structure or interaction between crystal layers. The term "nanoparticle" means a particle having a minimum particle diameter of less than 1 μm, for example, in the range of 0.1 nm or more and less than 1 μm. A nanoparticle typically means a particle having a maximum dimension of 5 μm or less, more preferably in the range of 3 nm to 2 μm. Note that the "minimum diameter" is determined by the minimum dimension passing through the center of gravity of the particle, and the "maximum dimension" is determined by the longest line segment that can be set within the particle. Also, the term "substantially parallel" is used to mean that the difference in their directions is limited to 10° or less, particularly 5° or less. The term "self-assembled" or "self-assembly" is used to mean that semiconductor nanoparticles self-organize and arrange with the interaction between particles as the driving force. Also, the term "functional group" is used as a term including halogen atoms.

[0021] <Conductive film> The conductive film of this embodiment contains semiconductor nanoparticles as conductive elements. The conductive film includes an array portion of semiconductor nanoparticles. When observing a cross-section including the array portion, in the array portion, the semiconductor nanoparticles are arranged in a state of being separated from each other. In the array portion, the semiconductor nanoparticles may be arranged in a single row. The conductive film may include a plurality of array portions extending substantially parallel to each other, or may include a plurality of array portions intersecting each other or connected to each other at their ends. The conductive film may be such that in at least one of its cross-sections, an array portion in which the semiconductor nanoparticles are arranged in a single row in a state of being separated from each other appears.

[0022] The conductivity C1 measured along at least one direction of the conductive film is 7 S / cm or more. When the direction in which the conductivity C1 is measured is defined as the first direction, the conductivity C2 measured along a second direction different from the first direction may be, for example, less than 10% of the conductivity C1, particularly less than 1% (that is, C2 / C1 < 0.1, particularly C2 / C1 < 0.01). The first direction and the second direction may be orthogonal to each other. One of the features of the conductive film of this embodiment is the anisotropy of the conductivity. Here, the first direction and the second direction are, for example, one is a direction parallel to the film surface, that is, the film surface direction, and the other is a direction perpendicular to the film surface, that is, the film thickness direction. The lower limit of the conductivity C2 is not particularly limited, but is, for example, 2×10 -5 S / cm or more.

[0023] In a cross-section where an array portion of semiconductor nanoparticles is observed, the average distance between adjacent semiconductor nanoparticles is preferably 10 nm or less. The "average distance" of the semiconductor nanoparticles shall be determined by individually measuring the shortest distances between two adjacent particles that are spaced apart in the array portion of the semiconductor nanoparticles appearing in the film cross-section and taking the arithmetic mean thereof. As an example, the average distance can be determined by measuring the shortest distances between two adjacent particles that are spaced apart at 10 locations along the portion where the two particles face each other and taking the arithmetic mean (so-called 10-point average). The semiconductor nanoparticles adjacent to each other in the array portion in the above cross-section are preferably spaced apart such that the sides facing each other are substantially parallel. In the conductive film, the first direction in which a conductivity C1 of 7 S / cm or more is obtained may be parallel to the cross-section where the above-described array portion appears. The array portion may be formed by the self-assembly of semiconductor nanoparticles during the formation of the conductive film.

[0024] The conductive film may contain a compound attached to the semiconductor nanoparticles, that is, an attached compound. The attached compound is a compound different from the semiconductor constituting the semiconductor nanoparticles, typically an organic or inorganic compound not corresponding to a semiconductor, and is preferably a compound different from an attachment for protecting the semiconductor nanoparticles contained in a conductive ink, which is a dispersion of semiconductor nanoparticles, from aggregation. The molecular weight of the attached compound is preferably 300 or less, 200 or less, 150 or less, more preferably less than 110, and particularly preferably less than 60. The attached compound may have a functional group suitable for binding to the semiconductor nanoparticles, for example, a ligand capable of binding to a metal atom by a coordination bond. This functional group may be included as an ion constituting a salt. However, in this case, the molecular weight of the compound shall be calculated excluding the counter ion of the salt. Therefore, for example, the molecular weight of KSCN containing SCN that can be attached to semiconductor nanoparticles is calculated excluding K and is 58.1.

[0025] The three-dimensional shape of the semiconductor nanoparticles may be a columnar body and / or a polyhedron. The bottom surface of the columnar body is not particularly limited and may be, for example, a circle, an ellipse, or a polygon. The columnar body is typically a column with the same and parallel bottom surfaces, but is not limited thereto. For example, it may be a solid whose longitudinal cross-section cut along the plane passing through both bottom surfaces can be regarded as a quadrilateral or a quadrilateral. The polyhedron may be a regular polyhedron such as a cube, but is not limited thereto. One of the preferred three-dimensional shapes is a rod-shaped columnar body having a height that is 2 times or more, further 3 times or more, particularly 4 times or more the diameter of the circle when the bottom surface is regarded as a circle of the same area (hereinafter, such a shape is simply referred to as "rod-shaped"). However, it is not limited thereto, and the columnar body may be a disk-shaped columnar body having a height that is 1 / 2 times or less, further 1 / 3 times or less, particularly 1 / 4 times or less the diameter of the circle when the bottom surface is regarded as a circle of the same area (hereinafter, such a shape is simply referred to as "disk-shaped"). The three-dimensional shape of the semiconductor nanoparticles may be rod-shaped and / or disk-shaped.

[0026] The semiconductor nanoparticles may contain at least one selected from oxides, sulfides, selenides, and tellurides, may contain at least one selected from sulfides, selenides, and tellurides, and may be sulfides and / or selenides. However, for applications that require durability such as heat resistance, generally, semiconductor nanoparticles containing oxides are suitable.

[0027] FIG. 1 shows an example of a conductive film. The conductive film 1 is formed on the surface 7a of the substrate 7. FIG. 1 is a cross-section of the film when the conductive film 1 is cut along a direction perpendicular to the surface 7a. FIG. 2 shows the semiconductor nanoparticles 11 and 12 contained in the conductive film 1. The shape and arrangement of the semiconductor nanoparticles 11 and 12 as shown in FIG. 2 can be observed, for example, using TEM. The minimum diameter of the semiconductor nanoparticles 11 and 12 is less than 1 μm, for example, 500 nm or less, preferably 100 nm or less. In the present embodiment, an insulating material exists in the matrix 40 in which the semiconductor nanoparticles 11 and 12 do not exist.

[0028] Semiconductor nanoparticles 11 and 12 appear in the film cross-section of the conductive film 1 shown in Fig. 2. The semiconductor nanoparticles 11 in the film cross-section are substantially polygons with 5 or more vertices, specifically pentagons or hexagons. The semiconductor nanoparticles 12 in the film cross-section are substantially quadrilaterals. More specifically, the semiconductor nanoparticles 12 in the film cross-section are rectangles, and more specifically, rectangles in which the long side corresponding to the bottom surface is 2 times or more the short side corresponding to the height. The semiconductor nanoparticles 11 and 12 observed in this way are, for example, disk-shaped. However, the shape of the semiconductor nanoparticles in the film cross-section is not limited to the above, and may be, for example, a square, such as a circle, an ellipse, a triangle, or a quadrilateral other than a rectangle.

[0029] When the semiconductor nanoparticles 12 appearing in the film cross-section are rectangles, the length of the long side of the rectangle is, for example, 3 to 2000 nm, further 5 to 900 nm, and further 10 to 50 nm. The length of the short side of the semiconductor nanoparticles 12 is, for example, 2 to 100 nm, and further 3 to 20 nm. The ratio of the long side to the short side of the semiconductor nanoparticles 12 may be, for example, 2 or more.

[0030] The conductive film 1 includes array portions 21, 22, 23, and 24 in which the semiconductor nanoparticles 11 and 12 are arranged. In the array portions 21 to 24, the semiconductor nanoparticles are arranged in a line without contacting adjacent particles. In the array portions 21 and 22, substantially pentagonal or hexagonal semiconductor nanoparticles 11 are arranged, and in the array portions 23 and 24, substantially rectangular semiconductor nanoparticles 12 are arranged. There is no particular limitation on the number of semiconductor nanoparticles arranged in the array portion, and 3 or more, 7 or more, in some cases 10 or more, and further 20 or more semiconductor nanoparticles may be arranged in a line.

[0031] In the array portions 21 to 24, a straight line can be drawn passing through the semiconductor nanoparticles included in each array portion. In other words, each array portion is arranged along the array direction that is a straight line. However, in Fig. 2, only the array directions 33 and 34 of the array portions 23 and 24 are shown, and the illustration of other array directions is omitted. In addition, in the film cross-section of Fig. 2, array portions of semiconductor nanoparticles appear other than those shown, but the display is omitted for simplification.

[0032] In the array portions 23 and 24, the adjacent semiconductor nanoparticles 12 are spaced apart such that the sides facing each other are substantially parallel. In such an array portion, the average distance between adjacent semiconductor nanoparticles 12 is likely to be kept small. Since the gap between semiconductor nanoparticles is usually insulating, an array with a small distance between semiconductor nanoparticles is advantageous for realizing high conductivity. Further, in the array portions 23 and 24, the facing sides of the adjacent semiconductor nanoparticles 12 are the long sides of a rectangle. In an array structure where the opposing sides are relatively long, even when there is a partial disorder in the arrangement of the semiconductor nanoparticles 12, the portion where the semiconductor nanoparticles 12 are close to each other is likely to be maintained, and the arrangement is likely to be maintained over a long distance. This feature is also advantageous for realizing high conductivity.

[0033] The average distance between semiconductor nanoparticles is, for example, 10 nm or less, further 7 nm or less, and in some cases 5 nm or less, 3 nm or less, further 2 nm or less, and particularly preferably 1.8 nm or less. The average distance may be, for example, 0.3 nm or more, further 0.5 nm or more.

[0034] FIGS. 3 and 4 show cross-sections of another example of the conductive film. Only substantially pentagonal or hexagonal semiconductor nanoparticles 13 appear in the film cross-section of the conductive film 2. The semiconductor nanoparticles appearing in the film cross-section of the conductive film 3 are only rectangular semiconductor nanoparticles 14. In FIG. 4, in the array portions 25, 26, 27, 28, and 29 extending along the array directions 35, 36, 37, 38, and 39 that are substantially parallel to each other, rectangular semiconductor nanoparticles 14 are arranged. Also, in the array portions 61, 62, 63, and 64 extending along the array directions 71, 72, 73, and 74 that are not substantially parallel to the array directions 35 to 39 but are substantially parallel to each other, substantially rectangular semiconductor nanoparticles 14 are arranged. In the film cross-section of FIG. 4, there are a number of array portions in which substantially rectangular semiconductor nanoparticles are arranged. In these array portions, the semiconductor nanoparticles 14 are adjacent to each other while being spaced apart such that the facing sides are substantially parallel to each other, and are arranged in a line over a long distance. Such a film cross-section is advantageous for making the conductivity in the in-plane direction sufficiently high.

[0035] However, it should be noted that even in the conductive film 2 in which a film cross-section (FIG. 3) where an array portion in which rectangular semiconductor nanoparticles are arrayed is not observed, in a different film cross-section, for example, in a direction perpendicular to the plane of FIG. 3, an array portion in which rectangular semiconductor nanoparticles are arrayed may be observed. For example, a film in which the three-dimensional shape of the semiconductor nanoparticles 13 is disk-shaped and the particles adjacent in the height direction are arranged such that their bottom surfaces face each other while being separated from each other may have a film cross-section as shown in FIG. 4 depending on the cutting direction.

[0036] Although FIGS. 2 to 4 show the mode in which all the semiconductor nanoparticles 11 to 14 are separated from each other, in the present embodiment, as long as an array portion in which the semiconductor nanoparticles are separated from each other is included, a part of the semiconductor nanoparticles may be in contact with each other in another part. In practice, even if they are actually separated, it is necessary to note that the semiconductor nanoparticles may be observed in contact or overlapping due to the observation direction, the resolution of the equipment used for observation, or the like.

[0037] The arrangement states of the semiconductor nanoparticles in a region wider than FIGS. 2 to 4 are illustrated in FIGS. 8 and 9. As shown in these figures, the array portions of the semiconductor nanoparticles do not need to extend in the same direction. The paths formed by a plurality of array portions may be curved, bent, cross each other, or partially overlap. The paths formed by a plurality of array portions form conductive paths.

[0038] In the conductive films 1 to 3, there is a matrix 40 in which the semiconductor nanoparticles 11 to 14 do not exist. The matrix 40 contains a binder and other materials to be described later. Materials such as the binder are also interposed between the semiconductor nanoparticles adjacent to each other in the array portion. Note that all of the materials constituting the matrix 40 may be insulating, but at least a part of them may be conductive.

[0039] The matrix 40 constitutes an element that allows for the self - arranging of semiconductor nanoparticles 11 - 14. An appropriate arrangement of semiconductor nanoparticles 11 - 14 can cause anisotropy in the conductivity of the conductive films 1 - 3, and can raise the conductivity to a practical level for at least a specific direction. The matrix 40 can also be an element that contributes to the improvement of the light transmittance of the conductive films 1 - 3. The matrix 40 can also be an element that suppresses the decrease in conductivity due to the bending of the conductive films 1 - 3. In the cross - section where the arranged portion of the semiconductor nanoparticles is observed, the matrix 40 where no semiconductor nanoparticles are present may occupy 20% or more, 30% or more, and even 40% or more of the whole, or may be 90% or less, and even 80% or less.

[0040] It is preferable that the conductive films 1 - 3 contain a compound attached to the semiconductor nanoparticles 11 - 14. This compound can also be interposed between adjacent semiconductor nanoparticles in the arranged portion. In order to keep the interval between the semiconductor nanoparticles narrow, it is preferable that the molecular weight of the compound is small. However, the compound attached to the semiconductor nanoparticles can be removed or reduced after film formation, for example, by heating. In particular, compounds with a small molecular weight such as hydrazine tend to disappear from the conductive film over time without intentional heating, so - called volatilization.

[0041] The conductivity C1 of the conductive film is 7 S / cm or more, further 10 S / cm or more, preferably 20 S / cm or more, more preferably 50 S / cm or more, still more preferably 100 S / cm or more, particularly preferably 150 S / cm or more, and in some cases 180 S / cm or more. The conductivity C1 may be obtained by measuring along at least one direction. This direction may be the film - plane direction parallel to the surface of the film, or the film - thickness direction perpendicular to the surface of the film. In practical use, a high conductivity of the conductive film is often required for a specific direction. For example, in a very thin conductive film, since the length in the film - plane direction is much larger than the film thickness, improving the conductivity in the film - plane direction often substantially solves practical problems.

[0042] As can be understood from the above, the conductivity of the conductive films 1 to 3 can have anisotropy resulting from the arrangement state of the semiconductor nanoparticles. The conductive film according to the present embodiment may be a film in which the conductivity C1 is measured along the first direction and the conductivity C2 lower than the conductivity C1 is measured along the second direction. When the first direction is the film surface direction, the second direction may be the film thickness direction. When the first direction is the film thickness direction, the second direction may be the film surface direction.

[0043] The conductivity C2 may be, for example, less than 10% of the conductivity C1, less than 1% of the conductivity C1, further less than 0.1% of the conductivity C1, particularly less than 0.001% of the conductivity C1, and in some cases less than 0.0001% of the conductivity C1. However, by appropriately arranging the semiconductor nanoparticles or narrowing the interval between the semiconductor nanoparticles, it becomes possible to improve not only the conductivity C1 but also the conductivity C2. The conductivity C2 is, for example, 2×10 -5 S / cm or more, further 1×10 -4 S / cm or more, particularly 1×10 -3 S / cm or more, and in some cases 1×10 -2 S / cm or more, further 1×10 -1 S / cm or more, particularly 1 S / cm or more. However, the conductive film of the present embodiment does not necessarily require significant anisotropy of conductivity.

[0044] Disorder in the arrangement of the semiconductor nanoparticles inhibits the achievement of the above-described high conductivity. In order to prevent the disorder in the arrangement, for example, it is desirable to sufficiently contain a compound that can adhere to the semiconductor nanoparticles in the dispersion used as the conductive ink for forming the conductive film. In a film in which the arrangement of the semiconductor nanoparticles is disordered, not only the conductivity C1 but also the conductivity C2 tends to decrease.

[0045] The direction dependence of the conductivity of the conductive film is affected by at least the affinity of the semiconductor nanoparticles for the surface of the substrate and the three-dimensional shape of the semiconductor nanoparticles. For example, semiconductor nanoparticles having a disk-shaped three-dimensional shape are arranged such that the disk surface is substantially perpendicular to the surface of the substrate on the surface of the substrate having a low affinity for the semiconductor nanoparticles. These semiconductor nanoparticles are arranged such that the disk surface is substantially parallel to the surface of the substrate on the surface of the substrate having a high affinity for the semiconductor nanoparticles. Also, for example, semiconductor nanoparticles having a rod-shaped three-dimensional shape are arranged such that the axial direction (major axis direction) of the rod is substantially perpendicular to the surface of the substrate on the surface of the substrate having a low affinity for the semiconductor nanoparticles, in other words, such that the rod stands on the surface. These semiconductor nanoparticles are arranged such that the axial direction of the rod is substantially parallel to the surface of the substrate on the surface of the substrate having a high affinity for the semiconductor nanoparticles, in other words, such that the rod lies down.

[0046] In order to control the direction dependence of the conductivity of the conductive film through the arrangement of the semiconductor nanoparticles, it is advisable to appropriately select the substrate to be used or to adjust the affinity of the surface of the substrate. For example, in order to arrange rod-shaped semiconductor nanoparticles on the surface of a substrate having a low affinity for the semiconductor nanoparticles such that the major axis direction of the rod is substantially parallel to the surface, it is advisable to previously coat the surface of the substrate with a material having a high affinity for the semiconductor nanoparticles. This arrangement is suitable for forming a conductive film having a relatively high conductivity C1 in the film thickness direction.

[0047] The light transmittance of the conductive film at a wavelength of 650 nm is, for example, 80% or more, further 85% or more, preferably 90% or more, more preferably 92% or more. A conductive film having such a high light transmittance may be called a transparent conductive film. However, the light transmittance of the conductive film at the same wavelength may be about 50 to 80%, and in some applications, 60% or more may be sufficient. Also, the light transmittance of the conductive film in the visible light region (region having a wavelength of 400 to 800 nm) is preferably, for example, 50% or more overall. Thereby, a substantially transparent conductive film can be obtained.

[0048] Similarly, the light transmittance of the conductive film at a wavelength of 550 nm is, for example, 80% or more, further 85% or more, preferably 90% or more, and more preferably 92% or more. The light transmittance of the conductive film at the same wavelength may be about 50 - 80%, and in some applications, 60% or more may be sufficient.

[0049] The film thickness of the conductive film is not particularly limited and may be appropriately set according to the application. For example, it is 5 - 5000 nm, 5 - 2000 nm, further 10 - 1000 nm, and particularly 100 - 800 nm.

[0050] The conductivity of the conductive film of this embodiment can have excellent folding resistance. In a conventional conductive film where conductive elements are in contact with each other to form a conductive path, the conductivity is likely to decrease due to bending. For example, as disclosed in FIG. 7 of Non-Patent Document 1, the conductivity of a conductive film containing silver nanowires in contact with each other as conductive elements often significantly decreases after about 300 - 400 bends. In contrast, in the conductive film of this embodiment, since semiconductor nanoparticles, which are conductive elements, form a conductive path while being separated from each other, the conductivity is less likely to decrease even when bending is repeated. As will be described later, in an example of the conductive film of this embodiment, even when bending is repeated hundreds of times or more, even 1000 times, the result is that the conductivity does not significantly decrease (see FIG. 11). To prevent such a decrease in the conductivity of a conductive film containing silver nanowires to this extent, it is necessary to melt and integrate the silver nanowires by photonic curing. As shown in FIG. 7 of Non-Patent Document 1, even after photonic curing, if bent more than about 900 times, the conductivity of the silver nanowires rapidly decreases. The conductive film of this embodiment takes advantage of its excellent folding resistance and is suitable for use in flexible devices.

[0051] When the following bending test is performed on the conductive film of this embodiment, the resistance change rate calculated by (|R2 - R1| / R1)×100 from the resistivity R1 before the test and the resistivity R2 after the test can be 30% or less, further 20% or less, and particularly 10% or less. However, in the bending test, the test piece on which the conductive film is formed is bent so that the bending angle is 180° and the radius of curvature of the bent portion is 5 cm or less, and then bent in the same manner on the opposite side. This is counted as one time and repeated 500 times, 800 times if necessary, and even 1000 times. The radius of curvature is usually preferably set to 5 cm. However, if it is possible to bend it more severely, as a more severe bending test, the radius of curvature may be set to less than 5 cm, for example, 1 cm, and in some cases, 5 mm. In addition, the resistivity R1 used for measurement is preferably 7 S / cm or more in terms of conductivity.

[0052] As shown in FIG. 10, for each bending test, the test piece 100 is bent once on both sides. The radius of curvature r of the bent portion 101 is determined at the deepest part 102 of the bent portion 101. In the bent state, the ends 103 of the test piece 100 are held parallel to each other so that the bending angle is 180°.

[0053] The conductive film of this embodiment can have excellent weather resistance. For example, in a conductive film containing silver nanowires as a conductive element, oxidation and migration progress in a high-temperature and high-humidity environment, and the conductivity rapidly decreases unless the conductive film is coated by an overcoat. On the contrary, since the conductive film of this embodiment uses semiconductor nanoparticles as a conductive element, its conductivity is hardly affected even when the surface of the film is exposed to a high-temperature and high-humidity atmosphere.

[0054] <Constituents of the conductive film> (Semiconductor nanoparticles) The semiconductor nanoparticles preferably contain at least one selected from compound semiconductors, specifically oxides, sulfides, selenides, and tellurides. The semiconductor nanoparticles may be composed of a semiconductor corresponding to a metal compound. In addition, trace components, particularly components for improving conductivity called dopants, may be added to the semiconductor nanoparticles.

[0055] Preferred oxides include indium oxide, zinc oxide, tungsten oxide, molybdenum oxide, cadmium oxide, copper oxide, vanadium oxide, and copper gallium oxide. Preferred sulfides include copper sulfide and indium copper sulfide. Preferred selenides include copper selenide. Preferred tellurides include copper telluride.

[0056] The semiconductor nanoparticles may be crystalline or amorphous, but when they contain crystals, the crystal structure may affect their conductivity. Also, the type of crystal can affect the three-dimensional shape of the semiconductor nanoparticles. Suitable crystal structures vary depending on the type of semiconductor nanoparticles. For example, copper sulfide preferably contains at least one selected from the group consisting of covellite, anilite, roxybite, digenite, and djuleite, particularly covellite and / or roxybite. Nanoparticles containing copper sulfide may contain only at least one crystal selected from the above.

[0057] The semiconductor nanoparticles preferably have a three-dimensional shape that results in a local ordered structure by self-assembly. Specifically, this three-dimensional shape is a shape having a cross-section in which substantially parallel opposite sides appear, and is typically a columnar body and / or a polyhedron. An example of the three-dimensional shape is a columnar body whose bottom surface is a circle, an ellipse, a polygon, or can approximate any of these. This shape may be the rod shape described above or a disk shape.

[0058] The content of the semiconductor nanoparticles in the conductive film is not particularly limited, but when expressed as mass%, it is, for example, 5 to 98%, further 10 to 50%, preferably 20 to 40%.

[0059] (Binder) The conductive film may contain a binder together with semiconductor nanoparticles. The binder is a preferable component that can be interposed between the semiconductor nanoparticles to impart flexibility to the conductive film. The binder can also contribute to the improvement of the film-forming property of the conductive film, the proper arrangement of the nanoparticles, etc.

[0060] The binder preferably contains an adhesion compound attached to the semiconductor nanoparticles. The adhesion compound may contain a functional group that can bind to the semiconductor nanoparticles, for example, fluoride (F), chloride (Cl), bromide (Br), iodide (I), cyanide (CN), thiocyanate (SCN), isothiocyanate (NCS), hydroxide (OH), mercapto (SH), carbonyl (CO), amino (NR 3 ), nitrosyl (NO), nitrito (NO 2 ), phosphane (PR 3 ), carbene (R 2 C) and pyridine (NC 5 H 5 ) and may contain at least one selected therefrom. Here, each R is independently an organic residue or a hydrogen atom. As can be understood from the above examples, the functional group that can bind to the semiconductor nanoparticles may be other functional groups that can function as ligands to metal atoms or anions.

[0061] The adhesion compound may be an inorganic compound or an organic compound. Further, the adhesion compound may be a salt composed of an ion containing or consisting of the functional groups exemplified above and its counter ion. The adhesion compound may be hydrazine (H 2 NNH 2 ), ethylenediamine (H 2 NCH 2 CH 2 NH 2 ), ethylenedithiol (HSCH 2 CH 2 SH), mercaptopropionic acid (HSCH 2 CH 2 COOH), acetylacetonato (H 3 CCOCHCOCH 3 ), aminobenzonitrile (NH 2 C6 H 4 Compounds having a plurality of the above functional groups, such as (CN), etc., may also be used.

[0062] The molecular weight of the adhesion compound is, for example, 300 or less, preferably 200 or less, more preferably 100 or less, still more preferably 80 or less, and in some cases less than 60. The lower limit of the molecular weight is not particularly limited, but is, for example, 20 or more, and further 30 or more. The use of an adhesion compound with a molecular weight not too large is suitable for precisely controlling the spacing between semiconductor nanoparticles.

[0063] The content of the adhesion compound in the conductive film may be appropriately adjusted depending on its type, but is expressed as the mass ratio of the adhesion compound to the total amount of the semiconductor nanoparticles and the adhesion compound, and may be, for example, 1% or more, further 2% or more, particularly 3% or more, and in some cases 5% or more, preferably 8% or more. The upper limit of this content is not particularly limited, but is 30% or less, and further 20% or less.

[0064] As the binder, materials other than the above-described adhesion compounds may be used. Examples of such compounds include various resins, specifically, polyvinyl alcohol, polyvinyl acetal, polyvinyl pyrrolidone, carboxymethyl cellulose, acrylic resin, polyvinyl acetate, polyethylene terephthalate, polystyrene, polyethylene, etc. In addition, depending on the requirements for forming the conductive film, its applications, etc., a pH adjuster, a colorant, a thickener, a surfactant, etc. may also be used.

[0065] <Device> The conductive film according to the present invention is suitable for use in various devices, particularly devices in which a conductive film having light transmissivity is used. Such devices include photovoltaic devices typified by solar cells, image display devices typified by liquid crystal displays and organic EL displays, heating devices typified by heated windshields, electromagnetic shielding devices typified by electromagnetic shielding windows and heat ray shielding windows, and the like. In these devices, the conductive film is used as an electrode film, an antistatic film, a heating film, an electromagnetic shielding film, or the like. By using a highly transparent conductive film for the above-described uses, advantages such as not interfering with the design of the product, not inhibiting information communication, and achieving invisibility can be obtained.

[0066] In the above-described devices, at least one electrode may be arranged in contact with the conductive film for energization or charge discharge. Examples of the electrode arrangement are shown in FIGS. 5 and 6. In the example shown in FIG. 5, a pair of electrodes 51 and 52 are arranged spaced apart in the film surface direction of the conductive film 4. By applying a potential difference between the electrodes 51 and 52, a current flows in the film surface direction of the conductive film 4. This conductive film can function as, for example, a heating film. The electrodes 51 and 52 do not necessarily need to be formed on the surface 7a of the base material 7 and may be formed on the surface 4a of the conductive film 4. In addition, only one electrode is sufficient for discharging charges from the conductive film for antistatic purposes rather than for heating.

[0067] In the example shown in FIG. 6, the conductive film 4 in contact with the electrode 53 is used as a light-transmissive electrode. For example, when the light 9 transmitted through the conductive film 4 is incident on the functional film 8, a potential difference is generated between the electrodes 53 and 54 due to the photoelectric conversion function of the functional film 8. Further, in another device, when a potential difference is applied between the conductive film 4 and the electrode 54, a voltage is applied to the functional film 8 along its film thickness direction (z direction in FIG. 6), and the functional film 8 emits light and emits light in the direction opposite to the incident light 9. In the example of FIG. 6, a transparent substrate such as a glass plate or a transparent resin plate can be used as the base material 7, and a metal film such as aluminum can be used as the electrode 54. However, the examples of the base material 7 and the electrode 54 are not limited to this. For example, the base material 7 may be a substrate having a thin film on its surface.

[0068] In the embodiment shown in FIG. 6, the electrode 53 extends along a direction perpendicular to the plane of the paper (the y direction in FIG. 6). In this case, in order to reduce the potential difference in the conductive film 4 due to the distance from the electrode 53, it is preferable that the conductive film 4 has a high conductivity C1 at least in the film surface direction (x direction) perpendicular to the direction in which the electrode extends.

[0069] In the embodiment shown in FIG. 6, when observed from the z direction perpendicular to the film surface of the conductive film 4, the area S1 of the region where the electrode 53 and the conductive film 4 overlap is less than 1 / 2, i.e., less than 50%, of the area S2 of the conductive film 4. The ratio of the area S1 to the area S2 may be, for example, 30% or less, further 20% or less, and in some cases 10% or less.

[0070] However, the shape and arrangement of the electrodes in the device are not limited to the examples shown in FIGS. 5 and 6.

[0071] In order to take advantage of the excellent fold resistance of the conductive film, a flexible device is also provided in this embodiment. The flexible device can be bent, for example, with a bending angle of 180° and a curvature radius of the bent portion of 5 cm or less, for example, 1 cm, and in some cases 5 mm, without damage while further including a substrate that supports the conductive film. For such a device, flexible substrates such as woven fabric, non-woven fabric, paper, and film are suitable. The resistance change rate of the conductive film measured by the above-described bending test of the device of this embodiment can be 30% or less, further 20% or less, and particularly 10% or less. However, the device of this embodiment may also be a rigid device lacking flexibility.

[0072] As described above, in this embodiment, the conductive film can have excellent durability. In order to take advantage of this property, in the device of this embodiment, at least a part of the conductive film may be exposed.

[0073] <Dispersion> The dispersion used to form the conductive film may be called a conductive ink. In accordance with this convention, the dispersion may be referred to as a conductive ink hereinafter in this specification. As can be understood from the above, the conductive ink does not need to be conductive by itself. The dispersion, which is the conductive ink, contains a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound, and the first compound exists as an attached compound attached to the semiconductor nanoparticles and a free compound free from the semiconductor nanoparticles, and satisfies at least one selected from the following i) to iv). It is desirable that the dispersion satisfies at least i). The dispersion may satisfy all of i) to iv). i) the ratio of the amount of the first compound present as a free compound to the amount of the first compound present as an attached compound is 1 or greater; ii) The ratio of the amount of the first compound to the total amount of the semiconductor nanoparticles and the first compound is 10% or more by mass. iii) The semiconductor nanoparticles contain at least one selected from an oxide, a sulfide, a selenide, and a telluride. iv) The semiconductor nanoparticles are columnar and / or polyhedral.

[0074] The conductive ink contains a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound. A part of the first compound is contained in the conductive ink as an attached compound attached to the semiconductor nanoparticles, and the rest of the first compound is contained in the conductive ink as a free compound liberated from the semiconductor nanoparticles. The first compound may be the same as the second compound to be attached to the semiconductor nanoparticles in the conductive film, but it is preferable that they are different compounds. This is because a compound that is desirable for improving the conductivity of the conductive film does not necessarily match a compound that is desirable for forming a conductive film in which the semiconductor nanoparticles are appropriately arranged from the conductive ink. As the first compound, a compound that is suitable for stably dispersing the semiconductor nanoparticles in the ink and for autonomously arranging the semiconductor nanoparticles during the formation of the conductive film can be used. The second compound can be introduced into the conductive film by replacing the first compound after the film is formed.

[0075] The self - arranging of semiconductor nanoparticles can be realized by using the interactions between semiconductor nanoparticles, specifically electrostatic force, van der Waals force, dipole force, dispersion force, etc. as driving forces. By using these as driving forces, as the dispersion medium is removed from the applied ink, it becomes possible to self - controllably arrange the semiconductor nanoparticles with a first compound intervening therebetween.

[0076] Similar to the second compound already described as the adhering compound, the first compound is preferably an inorganic or organic compound, particularly an organic compound, containing at least one, and in some cases a plurality, of the functional groups exemplified above. However, it is preferable that the molecular weight of the first compound is larger than that of the second compound. The molecular weight of the first compound is preferably 2000 or less, more preferably 1000 or less, still more preferably 500 or less, and is, for example, 60 - 300. The molecular weight of the first compound is also calculated based on the method described above when the first compound is a salt.

[0077] The content of the first compound in the conductive ink may be appropriately adjusted according to its type, but is preferably 10% or more, 15% or more, 16% or more, 17% or more, particularly 18% or more, and in some cases may be 20% or more, 25% or more, 28% or more, particularly 30% or more, when expressed as the ratio of the mass of the first compound to the total mass of the semiconductor nanoparticles and the first compound. The upper limit of this ratio is not particularly limited, but is, for example, 90% or less, 86% or less, and in some cases may be 75% or less. In order to self - arrange and appropriately arrange the semiconductor nanoparticles in the film after film formation, it is preferable to add more of the first compound than when the only purpose is to stably disperse the semiconductor nanoparticles in the ink. Conductive films formed from conductive inks lacking the first compound often have insufficient conductivity.

[0078] In order to appropriately arrange semiconductor nanoparticles, it is desirable that the conductive ink contains an appropriate amount of the first compound as a free compound. If the amount of the free compound is below the appropriate range, even if the semiconductor nanoparticles can secure their dispersed state in the conductive ink, they may partially aggregate. This aggregation can be a factor that inhibits the appropriate arrangement of the semiconductor nanoparticles in the conductive film. Since the state of attachment to the semiconductor nanoparticles is usually relatively more stable than the free state, the appropriate range of the amount of the free compound can be indicated by the ratio to the attached compound, specifically, the mass ratio or the molar ratio. The ratio of the amount of the first compound contained as the free compound to the amount of the first compound contained as the attached compound is preferably 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, particularly 8 or more, and may be 10 or more in some cases. The upper limit of this ratio is not particularly limited, but for example, it may be 100 or less, 50 or less, further 30 or less, and may be 28 or less, further 27 or less in some cases.

[0079] The dispersion of semiconductor nanoparticles may contain impurities derived from raw materials for the synthesis of semiconductor nanoparticles, additives added for the synthesis, etc. The impurities are typically unreacted raw materials. To remove these impurities, a solvent may be added and the impurities may be removed together with this solvent. As such a solvent, a polar solvent, particularly a polar organic solvent, may be used. As described later, usually, as the dispersion medium, a non-polar organic solvent or a polar organic solvent with low polarity is used. The removal of impurities can be carried out, for example, by a method including the following steps.

[0080] · Addition of solvent: A step of mixing a stock solution containing a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, the first compound, and impurities with a solvent to obtain a mixed solution. · Application of centrifugation: A step of applying centrifugation to the mixed solution at a predetermined rotational speed. · Removal of solvent: A step of removing the solvent together with at least a part of the above impurities from the mixed solution after centrifugation.

[0081] If the rotational speed of the centrifugation operation is too high, the amount of the first compound removed together with the solvent increases. Therefore, the rotational speed of the centrifugation operation is preferably less than 5000 rpm, particularly in the range of 500 to 4000 rpm. For the same reason, the centrifugation operation is preferably carried out at a temperature of the mixed solution near room temperature, specifically in the range of 10 to 30 °C. In addition, a poor solvent for the semiconductor nanoparticles is suitable as the polar solvent, and when the dispersion medium is a polar solvent, a polar solvent having a higher polarity than the dispersion medium is suitable. Specifically, as the polar solvent, a low-boiling solvent, for example, water, or a polar organic solvent such as an alcohol having 1 to 4 carbon atoms or acetone is suitable. In addition, although there is no particular limitation on the number of times the centrifugation operation is applied, generally 2 to 3 times are preferable.

[0082] Separate from the above-described conductive ink (which may be referred to as "first ink" when set with the second ink described later), it is desirable to prepare an ink (hereinafter sometimes referred to as "second ink") containing a second compound to replace the first compound. An ink set including the first ink and the second ink is convenient for forming a conductive film. The ink set includes, for example, the first ink, a first container containing the first ink, the second ink, and a second container containing the second ink. As described above, the first compound and the second compound are a combination of compounds in which the molecular weight of the latter is smaller than that of the former.

[0083] The conductive ink (first ink) and the second ink may contain a pH adjuster, a cosolvent, and other components. The other components may be the above-described components that the conductive film can contain, or may be volatile components that do not remain in the conductive film.

[0084] Preferred embodiments regarding the shape, crystal, etc. of the semiconductor nanoparticles are as described above. The content rate of the semiconductor nanoparticles in the conductive ink (first ink) is not particularly limited, but when expressed by mass%, for example, it is 1 to 70%, more preferably 5 to 50%, and preferably 10 to 20%. The dispersion medium in the conductive ink (first ink) is not particularly limited as long as it can disperse the semiconductor nanoparticles. For example, organic solvents such as toluene, hexane, octane, and chloroform can be preferably used. The solvent of the second ink is also not particularly limited as long as it can dissolve the second compound, and it is advisable to use one corresponding to the type of the second compound.

[0085] <Method for manufacturing a conductive film> The method for manufacturing a conductive film according to this embodiment includes the following first step and second step in this order. After the second step is carried out, the following third step and fourth step may be carried out. When the desired film thickness is not reached, the third step and fourth step can also be repeatedly carried out two or more times. When using the above-described ink set, the first ink is used as the conductive ink, and the second ink is used as a solution containing the second compound.

[0086] (First step) In the first step, a conductive ink containing semiconductor nanoparticles and a first compound is applied to the surface of a substrate to form a coating film. (Second step) In the second step, by bringing a solution containing the second compound into contact with the coating film formed in the first step, at least a part of the first compound is substituted with the second compound to obtain a conductive film. (Third step) In the third step, a conductive ink is applied to the surface of the formed conductive film to form an additional coating film. (Fourth step) In the fourth step, a solution containing the second compound is brought into contact with the formed additional coating film, and at least a part of the first compound contained in the additional coating film formed in the third step is substituted with the second compound to obtain a thickened conductive film.

[0087] The application of the conductive ink or solution in each step can be carried out by known coating methods such as spin coating, roll coating, flow coating, dip coating, etc.

[0088] Hereinafter, the present invention will be further described by way of examples, but the following description is not intended to limit the present invention to specific examples.

[0089] (Example A1) · Preparation of conductive ink 1.891 g of copper acetate, 1.13 g of 1,3-dibutyl-2-thiourea, and 10 ml of oleylamine were put into a three-necked flask, and nitrogen substitution was carried out while stirring. Next, using a mantle heater, the liquid temperature was raised to 80 °C and held for 1 hour. Then, when the liquid temperature dropped to 40 °C, 40 ml of chloroform was gradually added to the three-necked flask while dissolving the solid content.

[0090] The content of the three-necked flask was transferred to a centrifuge tube. After confirming that the solid matter was sufficiently dissolved in the centrifuge tube, 40 ml of ethanol was added. Further, a centrifugation operation was carried out under the conditions of 2000 rpm (revolutions per minute) for 10 minutes, and the supernatant was immediately discarded. Subsequently, after dissolving the precipitate in 5 ml of octane, 30 ml of ethanol was added again, and a centrifugation operation was carried out at a rotational speed of 2000 rpm for 5 minutes, and the precipitate was collected. The mass of the precipitate was measured, and based on this, octane was added so as to be 200 mg / ml, and copper sulfide nanoparticles were dispersed to obtain a conductive ink.

[0091] The conductive ink contains oleylamine, which is a compound capable of coordinating with copper sulfide nanoparticles, together with the copper sulfide nanoparticles. When the above precipitate was analyzed by thermogravimetric analysis (TGA) by thermogravimetric analysis, the ratio of the mass of oleylamine to the total mass of copper sulfide nanoparticles and oleylamine was 10%. This ratio was the same in the following examples.

[0092] · Formation of conductive film On a glass plate on which a comb-shaped electrode had been previously formed, 50 μl of a conductive ink (first ink) was applied using a spin coater to obtain a coating film. When applying, the concentration of the conductive ink was adjusted to 50 mg / ml. As the glass plate on which the comb-shaped electrode was formed, a commercially available product (manufactured by Drop Sens, G-IDEU5) with an electrode width and electrode interval of 5 μm or 10 μm, the number of pairs being 250 (when the electrode width is 5 μm) or 125 (when the electrode width is 10 μm), and the digit length being 6760 μm was used.

[0093] On the coating film, 200 μl of a solution containing KSCN (second ink) that becomes an adhesion compound was applied using a spin coater to obtain a conductive film. The solvent of this solution was octane, and the concentration of KSCN was 10% by mass. Due to the contact with the second ink, at least a part of the compound coordinated to the copper sulfide nanoparticles was substituted from oleylamine (first compound) to KSCN (second compound).

[0094] On the conductive film, an additional coating film was formed by the same film formation as above using the first ink, and then the substitution of the compound was carried out in the same manner as above using the second ink. Thus, a conductive film with an increased film thickness was obtained.

[0095] (Examples A2 to A4) A conductive film was produced in the same manner as in Example A1, except that the second compound in the second ink that becomes an adhesion compound was the compound shown in Table 1. At this time, the number of repetitions n of coating for thickening (n = 2 in Example A1) was also the number shown in Table 1.

[0096] (Examples A5 to A8) · Preparation of conductive ink 0.246 g of copper acetate and 20 ml of oleylamine were charged into a three-necked flask A, and the mixture was evacuated while stirring. Then, the flask A was heated using an oil bath to raise the liquid temperature to 160 °C and maintained in that state for 1 hour. The heating rate was 8 °C / min. On the other hand, 0.096 g of sulfur and 30 ml of 1-octadecene were charged into another three-necked flask B, and after repeatedly evacuating and replacing the atmosphere with nitrogen gas while stirring, nitrogen gas was introduced to maintain a nitrogen gas atmosphere. Then, the flask B was heated using an oil bath to raise the liquid temperature to 160 °C to dissolve sulfur. The heating rate was 5 °C / min. After leaving the flask B for 1 hour, nitrogen gas was introduced to maintain a nitrogen gas atmosphere.

[0097] The contents of flask A were transferred to a centrifuge tube, and the contents of flask B were added to the centrifuge tube using a syringe and held for 10 minutes. Then, the heater was turned off, and after the liquid temperature dropped to 40 °C, about 30 ml of hexane was added to the centrifuge tube. Next, after visually confirming that the generated solid had dissolved, 30 ml of ethanol was added, and a centrifugation operation was performed at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. Subsequently, after dissolving the precipitate in 5 ml of octane, 30 ml of ethanol was added again, and a centrifugation operation was performed again at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. The mass of the precipitate was measured, and based on this, octane was added to make it 200 mg / ml, and copper sulfide nanoparticles were dispersed to obtain a conductive ink.

[0098] · Formation of conductive film A conductive film was prepared in the same manner as in Example A1, except that the second compound in the second ink that becomes an adhering compound was the compound shown in Table 1. At this time, the number of repetitions n of coating for film thickening was also the number shown in Table 1.

[0099] (Example A9) Copper chloride (CuCl 2 ) 50.5 mg, copper nitrate (Cu(NO 3 ) 2 / 3H 2271.8 mg of O₂, 2.46 ml of oleylamine, 15 ml of 1-octadecene, and 6 ml of dodecanethiol were placed in a three-necked flask, and evacuation and replacement with nitrogen gas were repeated while stirring. Finally, evacuation was performed. Next, the three-necked flask was heated using a mantle heater to raise the liquid temperature to 100 °C and held in that state for 30 minutes. Subsequently, while raising the liquid temperature to 180 °C, 10 ml of t-dodecanethiol was injected from a syringe, held at 180 °C for 5 minutes, and then rapidly cooled using tap water.

[0100] The contents of the three-necked flask were transferred to a centrifuge tube, and about 30 ml of hexane was added to the centrifuge tube. Next, after visually confirming that the generated solid had dissolved, 15 ml of isopropanol and 15 ml of acetone were added, and centrifugation was performed at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. Subsequently, after dissolving the precipitate in 5 ml of octane, 30 ml of ethanol was added again, and centrifugation was performed again at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. The mass of the precipitate was measured, and based on this, octane was added to make it 200 mg / ml, and copper sulfide nanoparticles were dispersed to obtain conductive ink. After the liquid temperature dropped to 40 °C, about 30 ml of hexane was added to the centrifuge tube. Next, after visually confirming that the generated solid had dissolved, 30 ml of ethanol was added, and centrifugation was performed at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. Subsequently, after dissolving the precipitate in 5 ml of octane, 30 ml of ethanol was added again, and centrifugation was performed again at a rotational speed of 2000 rpm for 5 minutes to collect the precipitate. The mass of the precipitate was measured, and based on this, octane was added to make it 200 mg / ml, and copper sulfide nanoparticles were dispersed to obtain conductive ink.

[0101] · Formation of conductive film A conductive film was prepared in the same manner as in Example A1, except that the second compound in the second ink serving as the adhesion compound was the compound shown in Table 1. At this time, the number of coating repetitions n for film thickening was also the number shown in Table 1.

[0102] For the obtained conductive film, the conductivity and film thickness were measured, and further, the crystal system of copper sulfide contained in the copper sulfide nanoparticles was measured by X-ray diffraction. Also, for Examples A1 to A3, the light transmittance was also measured. The results are shown in Table 1 and FIG. 7. Note that the light transmittance in Table 1 is the value at a wavelength of 650 nm.

[0103]

Table 1

[0104] A conductive film was produced on the surface of a glass plate with an ITO film in the same manner as in Example A5, and a gold electrode was partially vapor-deposited on the surface of the conductive film. When the conductivity in the film thickness direction of this conductive film was measured, it was 9×10 -5 S / cm. For the conductive films obtained from the other examples as well, it was confirmed that the conductivity in the film thickness direction was lower than the conductivity in the film surface direction measured using a comb-shaped electrode and was significantly less than 1%. For the other examples as well, considering the arrangement of the nanoparticles, it is considered that the conductivity in the film thickness direction is considerably smaller than the conductivity in the film surface direction and does not exceed 10%.

[0105] Note that when observed using TEM, it was confirmed that the nanoparticles produced in Example A9 had a rod-like shape and were arranged such that the major axis direction was perpendicular to the surface of the substrate. On the other hand, it was confirmed that the nanoparticles produced in Examples A1 to A8 had a disk-like shape and were arranged such that the disk plane was perpendicular to the surface of the substrate. These crystal particles had a substantially rectangular cross-section and were arranged in close proximity to each other such that the opposing long sides were substantially parallel to each other. Also, it was confirmed that the arrangement direction of this arrangement extended in the film surface direction. Furthermore, in any of the examples, the average interval between the copper sulfide nanoparticles was 10 nm or less. For example, when a conductive film was produced on the surface of a glass plate on which a comb-shaped electrode was formed in the same manner as in Example A5, the average interval between the copper sulfide nanoparticles after substitution with EDT was 1.1 nm.

[0106] The results obtained by observing the conductive film formed from the conductive ink obtained in the same manner as above using TEM are shown in FIGS. 8 and 9. FIGS. 8 and 9 are images of observing the film surface of the conductive film.

[0107] As is clear from Table 1, roxbyite is a preferable crystal that can stably provide a relatively high conductivity. As far as the present inventor knows, this point is a finding that has not been known in the past. Also, covellite is a crystal that can provide a significantly improved conductivity, especially when combined with a compound having a small molecular weight. In other words, the conductivity obtained from covellite is easily affected by the adhering compound.

[0108] (Example A10) · Formation of conductive film A conductive film was fabricated on a borosilicate glass substrate in the same manner as in Example A1, except that hydrazine was used as the second compound in the second ink serving as the adhering compound. At this time, the number of coating repetitions for thickening was set to 15 times. Then, it was cut into a size of 10 mm x 10 mm to prepare a measurement sample. Thereafter, Au electrodes with a thickness of 100 to 200 nm were provided at the four corners of the surface of the measurement sample by vapor deposition. Then, using a sheet resistance measuring device Resi Test8400 (manufactured by Toyo Technica), the sheet resistance of the measurement sample was measured by the Van Der Pauw method such that four terminals were each in contact with the Au electrodes formed at the four corners. As a measurement result, the sheet resistance, which is the resistance in the film surface direction, was 100 Ω / sq. That is, in a conductive film of a certain size close to practical use, performance almost the same as that of ITO (indium tin oxide) was obtained. Different from ITO that needs to be formed by vapor deposition, this conductive film can be formed by coating, so its production is easier and its superiority was confirmed.

[0109] (Example B1) A conductive ink was obtained in the same manner as in Example A5, except that octadecene was used instead of octane as the organic solvent that was finally added to obtain the conductive ink. In this conductive ink, oleylamine is included as an attached compound attached to the copper sulfide nanoparticles and a free compound free from the copper sulfide nanoparticles. The ratio of the free compound to the attached compound in this conductive ink was determined as follows.

[0110] First, 5 ml of the conductive ink and then 45 ml of ethanol were put into a centrifuge tube, and centrifugation was carried out under the conditions of 2000 rpm for 10 minutes. Next, the obtained precipitate was evacuated to remove the residual solvent, and thermogravimetric analysis (TGA) was performed on the obtained dried solid to measure the amounts of the copper sulfide nanoparticles constituting the precipitate and oleylamine (attached compound) attached thereto, respectively. The ratio of the amount of oleylamine (attached compound) to the total amount of the copper sulfide nanoparticles and oleylamine (attached compound) was 10% on a mass basis. On the other hand, using an evaporator, only ethanol was removed from the supernatant obtained by the centrifugation operation, and based on the amount of the liquid after ethanol removal and the ratio of the amounts of oleylamine and octadecene added, the amount of oleylamine (free compound) free from the copper sulfide nanoparticles was calculated. Based on the above, when the ratio of the amount of the free compound to the amount of the attached compound was calculated, it was 21.4.

[0111] A conductive film was obtained in the same manner as in Example A5, except that the conductive ink of Example B1 was used. However, the film was formed to have a thickness of 135 nm. The measured conductivity is shown in Table 2.

[0112] (Example B2) The conductive ink prepared in Example A1 has undergone a total of two impurity removal steps by centrifugation. However, from the perspective of removing impurities such as unreacted compounds, it is desirable to further repeat the centrifugation operation. Considering this, in Example B2, after applying the centrifugation operation twice under the same conditions as in Example B1, the third centrifugation operation was carried out under the same conditions as the second centrifugation operation. Using the conductive ink obtained in the same manner as in Example B1 except for this, in the same manner as in Example B1, the ratio of the free compound to the adhered compound was determined, a conductive film was formed, and the conductivity was measured. The results are shown in Table 2.

[0113] (Comparative Example B3) The conductive ink prepared in Example A1 has carried out the impurity removal step by centrifugation under the condition of a rotation speed of 2000 rpm. However, from the perspective of removing impurities, it is also desirable to apply a centrifugation operation with a higher rotation speed. Considering this, in Comparative Example B3, the conditions of the centrifugation operation were changed to 8000 rpm for 2 minutes, and a total of three centrifugation operations were carried out. For the second and third washings, a mixed solution containing chloroform and ethanol in a ratio of 1:20 was introduced and carried out. Using the conductive ink obtained in the same manner as in Example B1 except for this, in the same manner as in Example B1, the ratio of the free compound to the adhered compound was determined, a conductive film was formed, and the conductivity was measured. The results are shown in Table 2.

[0114]

Table 2

[0115] In each of the conductive films obtained from Example B1, B2 and Comparative Example B3, the conductivity in the film surface direction was higher than that in the film thickness direction. Also, in Comparative Example B3, since the semiconductor nanoparticles were partially aggregated in the conductive ink, it is considered that the arrangement of the semiconductor nanoparticles was locally lost or became different over the entire conductive film. In such a film, sufficient conductivity cannot be obtained even in the direction in which the conductivity becomes relatively high (the film surface direction in the above example).

[0116] (Example C1) A conductive film was obtained in the same manner as in Example A6, except that a PET plate with a comb-shaped electrode was used instead of the glass plate with a comb-shaped electrode, and the number of coating times was changed to 5 times. As the PET plate with a comb-shaped electrode, a commercially available product (DRIP-P-IDEAU100 manufactured by Drop Sens) was used. The PET plate on which the conductive film was formed was bent 1000 times so that the radius of curvature of the bent portion was about 5 mm as shown in FIG. 10. The number of bends was counted as one set by continuously performing bends with the conductive film on the inside and bends with the conductive film on the outside. Also, the resistivity of the conductive film was measured using the comb-shaped electrode every 50 bends. FIG. 11 shows the change in the resistivity of the conductive film due to bending. The change rate of the resistivity was 10% or less.

[0117] (Example D1) A conductive film was obtained in the same manner as in Example A6, except that anisidine (molecular weight 123.2) was used as the second compound in the second ink that becomes the adhesion compound. With the conductive film exposed, the resistance values were measured at the time of creation and more than one and a half years (13140 hours) after creation. As a result, no increase in the resistivity of the conductive film was observed.

[0118] (Example D2) With the conductive film of Example A6 exposed, the resistance values were measured at the time of creation and one and a half years after creation. As a result, the resistance value, which was 44 Ω at the time of creation, became 78 Ω one and a half years after creation. Although there was an increase in the resistance value, it is considered that the increase in the resistance value was clearly suppressed compared to silver nanowires without overcoat.

Claims

1. A conductive film comprising an array portion of semiconductor nanoparticles, when observing a cross-section including the array portion, in the array portion, the semiconductor nanoparticles are arranged in a line with a spaced-apart state from each other, and the conductivity C1 measured along the film surface direction is 7 S / cm or more.

2. The conductive film according to claim 1, wherein in the cross-section, adjacent semiconductor nanoparticles in the array portion are spaced apart such that the direction of the sides facing each other is 10° or less.

3. Containing semiconductor nanoparticles as conductive elements, by the conductive elements, the conductivity C1 measured along the film surface direction is 7 S / cm or more, the conductivity C2 measured along the film thickness direction is less than 10% of the conductivity C1, and an anisotropic conductivity is exhibited.

4. The conductivity C2 is 2×10 -5 S / cm or more, the conductive film according to claim 3.

5. When a bending test is performed, the resistance change rate calculated by (|R2 - R1| / R1) × 100 based on the resistivity R1 before the test and the resistivity R2 after the test is 30% or less. The conductive film according to any one of claims 1 to 4. However, the bending test is a test in which a test piece on which the conductive film is formed is bent so that the bending angle is 180° and the curvature radius of the bent portion is 5 cm or less, and then bent in the same manner on the opposite side, and this is counted as one time and repeated 500 times.

6. The conductive film according to any one of claims 1 to 5, wherein the three-dimensional shape of the semiconductor nanoparticles is a columnar body and / or a polyhedron.

7. The conductive film according to any one of claims 1 to 6, wherein the semiconductor nanoparticles contain at least one selected from the group consisting of oxides, sulfides, selenides, and tellurides.

8. The conductive film according to any one of claims 1 to 7, wherein the semiconductor nanoparticles contain copper sulfide.

9. The conductive film according to claim 8, wherein the copper sulfide contains covellite and / or roxbyite.

10. Comprising the conductive film according to any one of claims 1 to 9, and the conductive film is provided as at least one functional film selected from an electrode film, an antistatic film, a heating film, and an electromagnetic wave shielding film.

11. A device comprising a conductive film containing semiconductor nanoparticles and at least one electrode in contact with the conductive film, wherein the conductive film satisfies the following a) and / or b). a) Comprising an array portion of the semiconductor nanoparticles, when observing a cross-section including the array portion, in the array portion, the semiconductor nanoparticles are arranged in a line with a spaced-apart state from each other, The conductivity C1 measured along the film surface direction is 7 S / cm or more. b) containing the semiconductor nanoparticles as a conductive element, by the conductive element, the conductivity C1 measured along the film surface direction is 7 S / cm or more, anisotropic conductivity is exhibited, where the conductivity C2 measured along the film thickness direction is less than 10% of the conductivity C1.

12. further comprising a substrate that supports the conductive film, The device according to claim 10 or 11, wherein the substrate can be bent so that the bending angle is 180° and the curvature radius of the bent portion is 5 cm or less without accompanying breakage.

13. A method for manufacturing a conductive film, wherein the conductive film is the conductive film according to any one of claims 1 to 9, a first step of applying a first ink, which includes a dispersion medium, semiconductor nanoparticles dispersed in the dispersion medium, and a first compound, and the first compound exists as an adhered compound attached to the semiconductor nanoparticles and a free compound free from the semiconductor nanoparticles, onto the surface of a substrate to form a coating film; a second step of bringing a second ink, which contains a second compound having a molecular weight smaller than that of the first compound and capable of substituting the first compound and attaching to the semiconductor nanoparticles, into contact with the coating film to substitute at least a part of the first compound in the coating film with the second compound. A method for manufacturing a conductive film comprising these steps.

Citation Information

Patent Citations

  • Oriented film

    JP2008115314A

  • Silver nanowires, production methods thereof, conductors and electronic devices including the same

    JP2017092036A

  • Transparent conductive porous nanocomposites and methods of fabrication thereof

    US20120305061A1

  • Materials and methods for conductive thin films

    US20180118960A1

  • Carbon nanotube dispersion liquid, conductor film and conductive film

    WO2015115102A1